Immunomodulatory Factors Control the Fate of Melanoma Tumor Initiating Cells. (28th June 2016) - Tuccitto, Alessandra; Tazzari, Marcella; Beretta, Valeria; Rini, Francesca; Miranda, Claudia; Greco, Angela; Santinami, Mario; Patuzzo, Roberto; Vergani, Barbara; Villa, Antonello; Manenti, Giacomo; Cleris, Loredana; et al.
Abstract: Melanoma is a highly heterogeneous tumor for which recent evidence supports a model of dynamic stemness. Melanoma cells might temporally acquire tumor-initiating properties or switch from a status of tumor-initiating cells (TICs) to a more differentiated one depending on the tumor context. However, factors driving these functional changes are still unknown. We focused on the role of cyto/chemokines in shaping TICs isolated directly from tumor specimens of two melanoma patients, namely Me14346S and Me15888S. We analyzed the secretion profile of TICs and of their corresponding melanoma differentiated cells and we tested the ability of cyto/chemokines to influence TIC self-renewal and differentiation. We found that TICs, grown in vitro as melanospheres, had a complex secretory profile as compared to their differentiated counterparts. Some factors, such as CCL-2 and IL-8, also produced by adherent melanoma cells and melanocytes did not influence TIC properties. Conversely, IL-6, released by differentiated cells, reduced TIC self-renewal and induced TIC differentiation while IL-10, produced by Me15888S, strongly promoted TIC self-renewal through paracrine/autocrine actions. Complete neutralization of IL-10 activity by gene silencing and antibody-mediated blocking of the IL-10Rα was required to sensitize Me15888S to IL-6-induced differentiation. For the first time these results show that functional heterogeneity of melanoma could be directly influenced by inflammatory and suppressive soluble factors, with IL-6 favoring TIC differentiation, and IL-10 supporting TIC self-renewal. Thus, understanding the tumor microenvironment (TME) role in modulating melanoma TIC phenotype is fundamental to identifying novel therapeutic targets to achieve long-lasting regression of metastatic melanoma. Abstract : Melanoma is a heterogeneous tumor that shows a model of dynamic stemness (1). Melanoma cells temporally acquire tumor-initiating properties or switch from a status of tumor-initiating cells (TICs) to a more differentiated one depending on the tumor context (2). TICs produce IL-10, while the differentiated cells release IL-6. The self-produced or exogenous IL-10 sustains self-renew and expansion of TICs (3) while IL-6 promotes their differentiation (4). The functional heterogeneity of melanoma can be influenced by inflammatory and suppressive factors released also by cells constituting the tumor microenviroment. Our in vitro and in vivo experiments suggest that anti-IL-10 antibodies (αIL10 mAb) or anti-IL-6 receptor α (tocilizumab) might represent drugs for novel therapeutic strategies in melanoma patients (5).